Public and Private Partnership Cooperation in Promoting Historical and Cultural Tourism in Nakhonphanom Province - WORAPHATTHIRAKUL, Paphatsorn; LATTANASOUVANNAPHONH, Champa; SOMSAMONE, Vilayphone; SENGDALA, Chansamone; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research aimed: 1) to study public and private partnership cooperation in promoting historical and cultural tourism in Nakhon Phanom province: 2) to study the pattern of public and private partnership cooperation in promoting historical and cultural tourism in Nakhon Phanom province: and 3) to suggest guidelines for public and private partnership cooperation in promoting historical and cultural tourism in Nakhon Phanom province. This was qualitative research, data collected through in-depth interviews with the key informants consisted of 30 people from the government sector, private sector, and public sector then brought leading up to the systematic, rational conclusion and reference theories to organize the data. The results indicated that: 1) public and private partnership used an integrated mechanism from all sectors to be consistent in order to achieve the goals of the quality of tourist destinations, tourism personnel and infrastructure for generating income and distributing income to the community under the Nakhon Phanom province development plan: 2) cooperation model found that (1) restoration and tourism development, (2) promoting tourism management to be responsible, (3) tourism promotion that was conducive to the learning process, (4) promoting the participation process of people and local communities and (5) public relations promotion, marketing, creating activities and forms of tourism: and 3) the suggestions for promoting important local religious and cultural tourism by pushing the tradition of the Illuminated Boat Procession as an international event, as well as improving the standards of facilities to accommodate tourists, aiming to become a tourist center city in the Greater Mekong Subregion (GMS).